Estimation of live food consumption for Hippocampus barbouri and Hippocampus kuda - Len, Yung Wung; Christianus, Annie; Worachananant, Suchai; Zakaria @ Ya, Muta Harah; Chong, Chou Min (Green Wave, 2020)
Seahorse is found worldwide in marine habitats such as the seagrass beds, coral reefs, mangroves and estuaries. Hippocampus barbouri and Hippocampus kuda are among the most traded seahorse species. In recent year, worldwide attention strongly support the establishment of seahorse aquaculture as to provide an alternative source of seahorse. However, the main bottleneck in succeeding seahorse aquaculture were problems faced in the culture of early stage juvenile, specifically the diet. The selection of suitable diet will contribute to the breeding success and larval rearing of seahorse. In this study the consumption of live food by new born, juvenile and adult seahorse were being investigated. H. barbouri and H. kuda commenced feeding at birth. The used of live food, namely the newly hatched Artemia nauplii was able support the growth and survival of new born and juvenile seahorses in specific tank systems. The results shows an increasing trend in which the increased of seahorse age and size (height), increases the average numbers of Artemia nauplii consumed. The minimum numbers of nauplii consumed by H. barbouri and H. kuda at 3 DAB with height 14.24±0.14 mm and 10.71±0.13 mm, were only 7 and 5 nauplii per feeding respectively. This study showed that Artemia nauplii can be used as live food for H. barbouri newborn stage to 28 DAB, while from newborn to 42 DAB for H. kuda. As for late juvenile stage of H. barbouri, at 90 DAB onwards, the used of adult Artemia instead of nauplii is highly recommended.